Modeling and Analysis of Various Operating Modes of 0,4 kV Low Voltage Electrical Networks - Muzaffar B. Khudayarov; Jakhongir A. Abdukhalimov; Doniyor S. Oltiboyev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: the annual increase in electricity demand, particularly the uneven distribution of loads in 0.4 kV low-voltage distribution networks, leads to a deterioration in power quality. In such networks, asymmetrical connection of consumers across phases often results in voltage unbalance, increased active and reactive power losses, and conditions that negatively affect the operating modes of electrical equipment. In practice, the design or operation of many low-voltage electrical networks is evaluated based on simplified calculation methods. This leads to an insufficient accounting of real operating modes, especially asymmetrical load conditions. Consequently, actual voltage levels in the network, phase-to-phase unbalance, and power losses are not accurately assessed. The results obtained are of significant scientific and practical importance for developing recommendations to reduce electricity losses, improve voltage quality, and ensure the optimal operation of low-voltage networks. Aim: the main objective is to model the symmetrical and asymmetrical operating modes of a 0.4 kV low-voltage electrical network using DIgSILENT PowerFactory software and to conduct a comprehensive analysis of the impact of phase load distribution on phase-to-phase voltage unbalance and active/reactive power losses in the network. Methods: computational modeling methods were used to study the operating modes of low-voltage networks. Results: Symmetrical and asymmetrical operating modes of the 0.4 kV low-voltage electrical network were modeled in the DIgSILENT PowerFactory software package, and their impact on the electrical network was evaluated. The results showed that the asymmetrical distribution of loads across phases in low-voltage electrical networks leads to a decrease in power quality and an increase in power losses.